ANALISIS TRANSPARANSI DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN SATU PINTU KABUPATEN BONE - Marjana Fahri (Al-Adalah: Jurnal Hukum dan Politik Islam, 2018)
Transparency of service is very important for government agencies in the provision of public services, because with the transparency of services so the public can easily find information or access about procedures in services provided olen government agencies. This study aims to describe, measure and analyze the Transparency of Public Service in the Office of Investment and Service of One Door of Bone Regency. This research is a qualitative research, approach method used is approach (social legal reserarch), data collection is done through interview, observation and documentation to informant in applying of transparency of public service. data analysis includes data reduction, data presentation and conclusion. The results of the research show that the application of transparency of the One Bint Department of Investment and Service Bone District has not been fully implemented in the indicator of service transparency expected by the service recipients such as Authorized and Responsible Officials there are still some authorities who have not yet fully know what they should do so much training is needed that can encourage transparency. Constraints faced by the internet network factors are not adequate so slow in the process of service delivery.